A Descriptive Study on Volatility in the USA Stock Markets and its Implications on Indian Stock Markets with Special Reference to Students of Management - Harsh Mohan Preenja; Dr. Shilpa Mishra (International Journal of Engineering and Management Research, 2023)
The USA stock market is the oldest stock market in the world, dating back to the 18 th century. It is known for its volatility, which can be influenced by a wide variety of factors, including economic indicators like GDP, inflation, and employment numbers, as well as geopolitical events, corporate earnings reports, and global economic trends. Other factors influencing the volatility are bond yields, commodity and oil prices and political events. Being the leading economic power in the world, it is natural that USA market trends heavily influence the Indian stock markets. This paper will analyse the volatility in the US stock markets and its implications on the Indian stock markets.